أوجه التعاون الأمريكي- الألماني وأثره على العلاقات بين الدولتين 1930-1932 - سكر خيون, بشرى (Journal of College of Education, 2018)
أوجه التعاون الأمريكي- الألماني وأثره على العلاقات بين الدولتين 1930-1932